Electric Behavior Modeling and Evaluation of New Lightweight Conductive Concrete - Swaked, Bassam Emad (2016)
A Master of Science thesis in Electrical Engineering by Bassam Emad Swaked entitled, "Electric Behavior Modeling and Evaluation of New Lightweight Conductive Concrete," submitted in November 2016. Thesis advisor is Dr. Nasser Qaddoumi and thesis co-advisor is Dr. Sherif Yehia. Soft and hard copy available.